Contextual and behavioral influences on uncertainty in obsessive-compulsive disorder. (January 2015) - Rotge, Jean-Yves; Langbour, Nicolas; Dilharreguy, Bixente; Bordessoulles, Martine; Guehl, Dominique; Bioulac, Bernard; Martin-Guehl, Corinne; Jaafari, Nematollah; Aouizerate, Bruno; Allard, Michele; Burbaud, Pierre
Abstract: Introduction: Behavioral adaptation generally follows the contextual changes arising from the consequences (rewards and punishments) of an action. According to the reciprocal determinism model, there is a mutual influence between external context, cognitive processes and behavior. The maladaptive behaviors observed in obsessive-compulsive disorder (OCD) have been hypothesized to result from the disruption of the interactions between these three entities. For this, we assessed the influence of error signals and checking behavior on prefrontal cortical functions during decision-making in 14 OCD patients and 14 matched healthy participants. Methods: We used a behavioral task designed to elicit intolerance of uncertainty (IU) followed by the free expression of checking behaviors, which was coupled with functional magnetic resonance imaging. Results: At the behavioral level, IU intensity was correlated to the number of checking behaviors in both checking OCD patients and healthy controls during decision-making. However, external error signals did not influence checking behaviors in OCD patients, whereas they appeared to trigger checking behaviors in healthy subjects. At the neural level, IU intensity was positively correlated with activation in the orbitofrontal cortex (OFC) in both the OCD and control groups. At the region of interest (ROI) level, error signals increased IU-related OFC activations; in contrast, checking behaviors contributed to decreasing these neural activations in the healthy subjects, but no such modulation was observed in the OCD patients. Conclusions: Our results show that IU-related OFC dysfunctions are not under the influence of the context and the behavioral response in OCD, suggesting that alterations of the dynamic features for this neural network may contribute to the expression of OCD symptoms.